An introduction to hospital sites selection and design - Firooz Jamali; Mir Sattar Sadrmousavi; Mehdi Eshlaghi (Tehran University of Medical Sciences, 2012)
Background: The hospital is an important element in the new public health. The health in the populations requires access to the medical and hospital services as well as preventive care and a healthy environment. This study attempts to review the important factors to be considered in the hospital sites selected and design in the urban, regional and country levels. Finally, suggestions have exhibited to the hospital sites selected and design for its optimum and efficiency. It's also suggests proposals for appropriate site selected and design of hospitals for optimum efficiency. Materials & Methods: This is a review article which documentary method and Internet search have been employed.Results: What principles do you use to decide on the location and layout of a new or expanded site selection? What information do you need to consider before selecting a site location? How do you maximize inherently safer design with minimal impact on the cost and schedule? How do you manage sitting issues when limited space is available? How do you address security concerns in a new site? These questions are considered cases in paper to attempt to answer it. Conclusion: To determine the feasibility of the project, the first consideration in the survey is to study the character, needs and possibilities of the community which the hospital is going to serve. The hospital facilities in the region should be studied in terms of: • Population of the region• Quality and number of hospitals• Patient and disease pattern• Cost of investigation and treatment • Physical and Environmental characteristics of the siteThis study considers the specific problems of creating a well distributed network of hospitals that deliver its services to the target population in minimal time, pollution and cost. The study has showed that if these criteria considered, it would assessed the extent to which authorities of hospital planning and administration have utilized in the planning.